Pemberdayaan Masyarakat melalui Pengolahan Jamu Tradisional dalam Mitigasi Penyakit Degeneratif dan Kemandirian Ekonomi di Desa Tenjonagara - Ristina Siti Sundari; Gina Mupidah; Silvia Nurlina (Journal of Empowerment Community, 2026)
Degenerative diseases such as gout and high cholesterol are quite prevalent in Indonesia, where modernization has led to changes in epidemiology and an increase in these cases, including in rural areas like Tenjonagara Village. Villagers often complain of these conditions, which are associated with changes in diets rich in purines and fats and decreased physical activity. The goal of this community service program is to improve the understanding and skills of the Tenjonagara Village community through the processing of traditional herbal medicine (jamu) as an effort to reduce the risk of degenerative diseases and create economic independence. Implementation activities include a diffusion of science and technology approach, interviews, counseling, socialization on the cultivation of Family Medicinal Plants (TOGA), and practical training on making herbal medicine to treat gout and cholesterol, involving women from the Family Welfare Movement (PKK) cadres. The results of this activity showed an increase in participants' understanding and skills in processing TOGA into herbal drinks. The community became more active in growing medicinal plants and reported a reduction in disease symptoms. Furthermore, there was a community desire to support the economic potential of the resulting herbal products.